Associations between grip strength and glycemic control in type 2 diabetes mellitus: an analysis of data from the 2014-2019 Korea National Health and Nutrition Examination Survey - Harim Choe; Hoyong Sung; Geon Hui Kim; On Lee; Hyo Youl Moon; Yeon Soo Kim (Epidemiology and Health, 2021)
OBJECTIVES Glycemic control is essential for preventing severe complications in patients with diabetes mellitus. This study investigated the association between grip strength and glycemic control in Korean adults with type 2 diabetes mellitus. METHODS From the Korea National Health and Nutrition Examination Survey, 2,498 participants aged over 19 years that patients with diabetes mellitus who did not have a history of cardiovascular disease or cancer were selected for analysis. Grip strength was assessed using a handheld dynamometer and was represented as age-specific and sex-specific tertiles. Multivariable logistic regression was performed to calculate the odds ratio (OR) and 95% confidence interval (CI) of glycemic control according to the grip strength tertiles. RESULTS A significantly lower probability (OR, 0.67; 95% CI, 0.47 to 0.97) for glycemic control was found in the lowest tertile of grip strength compared to the highest tertile. Furthermore, a subgroup analysis by sex only found significant associations between grip strength and glycemic control in males. CONCLUSIONS Lower grip strength was associated with poor glycemic control in patients with diabetes mellitus, especially in males. However, further studies are needed to confirm the causal relationship between grip strength and glycemic control.